South African review. - Khadiagala, Gilbert M.; Mosoetsa, Sarah; Pillay, Devan; Southall, Roger (Wits University Press, 2018)
Despite the transition from apartheid to democracy, South Africa is the most unequal country in the world. Its extremes of wealth and poverty undermine intensifying struggles for a better life for all. The wide-ranging essays in this sixth volume of the New South African Review demonstrate how the consequences of inequality extend throughout society and the political economy, crippling the quest for social justice, polarising the politics, skewing economic outcomes and bringing devastating environmental consequences in their wake. Contributors survey the extent and consequences of inequality across fields as diverse as education, disability, agrarian reform, nuclear geography and small towns, and tackle some of the most difficult social, political and economic issues. How has the quest for greater equality affected progressive political discourse? How has inequality reproduced itself, despite best intentions in social policy, to the detriment of the poor and the historically disadvantaged? How have shifts in mining and the financialisation of the economy reshaped the contours of inequality? How does inequality reach into the daily social life of South Africans, and shape the way in which they interact? How does the extent and shape of inequality in South Africa compare with that of other major countries of the global South which themselves are notorious for their extremes of wealth and poverty? South African extremes of inequality reflect increasing inequality globally, and The Crisis of Inequality will speak to all those – general readers, policy makers, researchers and students – who are demanding a more equal world.